Sportomics analyses of the exercise-induced impact on amino acid metabolism and acute-phase protein kinetics in female Olympic athletes - Muniz-Santos, R.; Bassini, A.; Falcão, J.; Prado, E.; Martin, L., III; Chandran, V.; Jurisica, I.; Cameron, L. C. (Nutrients, 2024)
Background Exercise can be used as a model to understand immunometabolism. Biological data on elite athletes are limited, especially for female athletes, including relevant data on acute-phase proteins and amino acid metabolism.